2011
DOI: 10.1007/s10683-011-9303-7
|View full text |Cite
|
Sign up to set email alerts
|

A field experiment on the impact of weather shocks and insurance on risky investment

Abstract: We conduct a framed field experiment in rural Ethiopia to test the seminal hypothesis that insurance provision induces farmers to take greater, yet profitable, risks. Farmers participated in a game protocol in which they were asked to make a simple decision: whether or not to purchase fertilizer and if so, how many bags. The return to fertilizer was dependent on a stochastic weather draw made in each round of the game. In later rounds a random selection of farmers made this decision in the presence of a styliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 53 publications
2
61
1
Order By: Relevance
“…They found that in the anticipation of possible negative covariate shocks, households, especially poorer ones, opt for less risky technologies and portfolios in order to avoid permanent damage. Fertilizer application rates were also found to be lower due to downside risk in consumption (see also Hill and Viceisza, 2012).…”
Section: Limitations and Way Forwardmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that in the anticipation of possible negative covariate shocks, households, especially poorer ones, opt for less risky technologies and portfolios in order to avoid permanent damage. Fertilizer application rates were also found to be lower due to downside risk in consumption (see also Hill and Viceisza, 2012).…”
Section: Limitations and Way Forwardmentioning
confidence: 97%
“…Consequently, from a demand side perspective an index insurance product that enables farmers to obtain credits for fertilizer use protection against malnutrition seems attractive. For example, a field experiment by Hill and Viceisza (2012) found that insurance has a positive impact on Table 1 Mitscherlich-Baule crop response function.…”
Section: Risk Financing and Growthmentioning
confidence: 99%
“…Given that the series of events was the same in each of the treatments, the treatment effect can be identified by comparing the outcomes without controlling for differences in realizations of states of nature. This would have been necessary if the realization of events was truly random and subjects maintained a heuristic understanding of probabilities (e.g., Hill and Viceisza, 2011).…”
Section: Implementation and Proceduresmentioning
confidence: 99%
“…31 Several studies do, however, find that weather insurance can help farmers make riskier decisions (e.g., Vargas Hill and Viceisza, 2010;Cai, 2012;Karlan et al, 2012;Mobarak and Rosenzweig, 2012;Cole et al, 2013a (1) and (3) show the control group mean for the full sample and the sample excluding the attritors respectively, with the standard deviation in parenthesis. Columns (2) and (4) show the coefficients of regressions of the pre-treatment variable in question on a treatment dummy, with robust standard errors, clustered at the group level, in parenthesis.…”
mentioning
confidence: 99%